The equation that gives all the points (x, y) that are at the same distance from (4, 1) as from the x-axis is:
y = (1/2)*(x - 4)^2 + 1/2.
First, remember that for a point (x, y), the distance to the x-axis is equal to y.
And we also know that the distance between two points (x₁, y₁) and (x₂, y₂) is:
[tex]d = \sqrt{(y_2 - y_1)^2 + (x_2 - x_1)^2}[/tex]
The distance between (x, y) and (4, 1) is:
[tex]d = \sqrt{(x - 4)^2 + (y - 1)^2}[/tex]
And this must be equal to y, so we can write:
[tex]y = \sqrt{(x - 4)^2 + (y - 1)^2}[/tex]
This is the equation we need to solve.
We will get:
[tex]y^2 = (x - 4)^2 + (y - 1)^2\\\\y^2 = (x - 4)^2 + y^2 - 2y + 1\\\\0 = (x - 4)^2 - 2y + 1\\\\2y = (x - 4)^2 + 1\\\\y = (1/2)*(x - 4)^2 + 1/2[/tex]
This equation gives all the points (x, y) that are at the same distance of (4, 1) as from the x-axis.
If you want to learn more about distances between points, you can read:
https://brainly.com/question/7243416